The Influence Of Work Evironment, Work Discipline And Intrinstic Motivation On Employee Wonk Productivity PT Panca Guna Saudara - Regina Ira Lawang; Didik Subiyanto; Kusuma Chandra Kirana (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to examine the influence of the work environment, work discipline, and intrinsic work motivation on employee work productivity. The Population of PT Panca Guna Saudara employees. Sampling technique used in this research was purposive sampling with a total of 100 employees as respondents, who were then analyzed using SPSS version 25. Data processing was carried out using multiple linear regression analysis. The results of the research show that the work environment variables, work discipline, and intrinsic work motivation together influence the work productivity of employees at PT Panca Guna Saudara